Effect of LMP-1 and mutant p53 on the Prognosis of Undifferentiated Type of Nasopharyngeal Carcinoma - Atikah, Atikah; Sadhana, Udadi; Miranti, Ika Pawitra; Puspasari, Dik; Karlowee, Vega (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2022)
Undifferentiated carcinoma is a subtype of NPC with a higher EBV antibody titer than healthy people. The carcinogenic effect of EBV involves LMP-1 associated with poor prognosis, and mutant p53 predicts tumor recurrence. This study aims to assess the effect of LMP-1 and mutant p53 on the prognosis of NPC patients. 40 paraffin blocks were stained with LMP-1 and p53 mutant. LMP-1 was positive when the cytoplasm and tumor cell membranes were brown, and mutant p53 was positive for the brown tumor cell nucleus. Pearson correlation test was performed. Most respondents were in the age group 40 years, males, regional lymph node involvement (N) in group N1, and no metastasis (M). The expression levels of LMP-1 and mutant p53 were strongly positive. The study showed the correlation between LMP-1 with age (p 0.327), gender (p 0.599), category N (p 0.512), category M (p 0.019) and the correlation between mutant p53 with age (p 0.329), gender (p 0.981), category N (p 0.013), category M (p 0.705). LMP-1 expression with mutant p53 (p 0.760). It can be concluded that LMP-1 and mutant p53 could be used as prognostic factors in NPC patients.